(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents the results to assess the dynamics of reproductive losses in Bukhara during the period of 2020 to 2022. Decrease in reproductive losses is an important reserve for improving demographic situation. Reproductive losses are the losses of conception product at all the stages of fetus development, caused by spontaneous and stimulated abortion, dead birth as well as death of first-year of life children. For the analyzed period, increase in the number of labors by 8 times and reduction in the number of medical abortions (losses – 71 %) was noted. In the structure of pregnancies with abortive outcome, the share of extrauterine pregnancy remains at the same level. A threefold decrease in dead births is observed. Reproductive losses are the following: I place – early miscarriage; II – extrauterine pregnancy; III – late miscarriage; IV – mortаlity. The place, occupied by the losses of desired pregnancies, becomes more and more significant. That is why we need to accentuate specialists’ attention on the problems of family planning, pregravid preparation and management of pregnancy at early terms.